PROSES PENGOLAHAN PAKAN UNGGAS DARI TEPUNG IKAN DI DESA SENTANG KECAMATAN TELUK MENGKUDU KABUPATEN SERDANG BEDAGAI: Indonesia - Harahap, Hamidah; Manurung, Renita; Nasution, Halimatuddahliana; Masyithah, Zuhrina; Yustira, Ayuni (UII, 2024)
This research aims to create a poultry feed formulation that complies with SNI 01-3931-2006 standards regarding broiler poultry feed, where the process of making poultry feed includes four main ingredients, namely fish meal, corn, rice bran and vitamins. In this research there are two main processes, namely the process of making fish meal and the process of making poultry feed. Fish meal is a raw material for making poultry feed because it has high protein content. Fish meal in the process of making poultry feed is obtained from processing fish caught at sea by fishermen. This research activity was carried out in Sentang Village, Teluk Mengkudu District, Serdang Berdagai Regency. This location was chosen because it is near the sea and has abundant natural resource potential for marine products. The resulting poultry feed is then analyzed including water content, protein, oil content, ash content, crude fiber, calcium and protein. Poultry feed analysis was carried out in the Palm Oil Research Center (PPKS) laboratory. The analysis results showed water content 30.90%, protein 11.70%, oil content 3.17%, ash content 5.16%, crude fiber 17.32%, calcium 182.41 ppm and phosphorus <0.01 ppm.